1996
DOI: 10.1063/1.117397
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of real time spectroellipsometry and atomic force microscopy measurements of surface roughness on amorphous semiconductor thin films

Abstract: We have correlated the results of real time spectroellipsometry (SE) and ex situ atomic force microscopy (AFM) measurements of surface roughness on amorphous semiconductor thin films. Roughness layer thicknesses deduced from real time SE, using a conventional approach based on the Bruggeman effective medium theory, closely obey a relationship of the form: ds(SE)≊1.5 drms(AFM)+4 Å, for 10≤dS(SE)<100 Å, where drms(AFM) is the root-mean-square roughness from AFM. The slope and intercept of this relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
33
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(43 citation statements)
references
References 2 publications
9
33
1
Order By: Relevance
“…It is seen that the roughness drops monotonically as the Ni fraction is increased. Roughness data obtained by AFM and ellipsometry in general show a quantitative and linear relation 22,23 and the results in Fig. 2 are in line with the magnitude of the AFM-determined protrusion height shown in Fig.…”
Section: B Datasupporting
confidence: 70%
“…It is seen that the roughness drops monotonically as the Ni fraction is increased. Roughness data obtained by AFM and ellipsometry in general show a quantitative and linear relation 22,23 and the results in Fig. 2 are in line with the magnitude of the AFM-determined protrusion height shown in Fig.…”
Section: B Datasupporting
confidence: 70%
“…From Table I, we observed that the void percentage increases with the sol concentration and saturated at 50% for sol of 0.12 M. This indicates that at low concentration the surface roughness is small so that the contribution is mainly due to pores while at high concentration the void percentage is mostly due to the surface roughness. Unlike the relation obtained in semiconductor, 14 an modified correlation of ellipsometry and AFM measurements of surface roughness was observed in our measurement:…”
Section: Resultscontrasting
confidence: 42%
“…This justifies the two-layer model used for the analysis of ellipsometry data. It may be mentioned that Koh et al 72 have also…”
mentioning
confidence: 99%